2016
DOI: 10.3109/00016357.2016.1151547
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion traits and orthodontic treatment in a Finnish adult population

Abstract: Objective The aim of the study was to examine the prevalence of malocclusion traits and the extent of orthodontic treatment in a Finnish adult population. Materials and methods The study population comprised subjects (n = 1964) from the Northern Finland Birth Cohort 1966 living in the city of Oulu and within 100 km of it. A clinical oral and dental examination with registration of occlusion was carried out in 2012 in connection with a 46-year follow-up survey. Data on previous orthodontic treatment were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
4
30
0
1
Order By: Relevance
“…The motivating factor for females to seek orthodontic treatment seems to be for enhancing facial aesthetics [4]. Similar trends have been reported worldwide [5][6][7].…”
Section: Introductionsupporting
confidence: 60%
“…The motivating factor for females to seek orthodontic treatment seems to be for enhancing facial aesthetics [4]. Similar trends have been reported worldwide [5][6][7].…”
Section: Introductionsupporting
confidence: 60%
“…Malocclusion also refers to noncompliance or incorrect pairing between upper and lower maxilla between dental arch and as one of the problems that endangers oro-facial system and can create problems in this system, such as loss of function, loss of beauty, temporomandibular problems, and periodontal diseases. 1,10,12,13 One of the important factors in the treatment and prevention of any disease is determination of epidemiological indicators of that disease, i.e., malocclusion, which is not exceptional from this regulation. 8 A treatment way or prevention method of a disease can never be known to be effective in controlling that disease, except a significant change is made over time in the prevalence of that disease.…”
Section: Discussionmentioning
confidence: 99%
“…3 Similar studies were carried out in different countries in which their results are different. 1,9,10 Owing to the impact of environmental and genetic factors and the role of geographic areas in the dispersion of types of malocclusion in different countries, various distribution and prevalence of malocclusions have been reported. 10 In Iran, in spite of few studies on this area, there is still the need to evaluate the prevalence in different cities and treatment centers, from different aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant differences were found for the other aspects of malocclusion reported in the NHANES . Other, smaller scale, studies have found that males have significantly deeper bites, greater buccal crossbite and greater reverse overjet than females . Once again, sex differences in the prevalence of malocclusion among US adults have not been evaluated statistically.…”
Section: Introductionmentioning
confidence: 88%